Spacecraft Structures Conference 2014
DOI: 10.2514/6.2014-1036
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Spiral Folding for Flat Membrane Apertures

Abstract: A folding concept has been developed which allows a precision membrane aperture to be elastically stowed with a very high compaction ratio without creasing. The lack of creasing is extremely important when the membrane is used in RF or diffractive optics applications because of its effect on the relative placement of surface features. This concept utilizes the spiral wrapped folding approach with a reduced thickness membrane in the folding hinge lines and through-hole strain relief at the intersecting folds. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Another challenge is that two elastic folds in different directions will still cause plastic deformation at the point of intersection. This can be avoided by removing enough material around this point, leaving a hole that accomodates the presence of the two folds [6].…”
Section: Membrane Folding and Creasingmentioning
confidence: 99%
“…Another challenge is that two elastic folds in different directions will still cause plastic deformation at the point of intersection. This can be avoided by removing enough material around this point, leaving a hole that accomodates the presence of the two folds [6].…”
Section: Membrane Folding and Creasingmentioning
confidence: 99%
“…As discussed previously, this modeling assumption allows membrane dynamics be treated as external perturbations. In order to prevent control performance deterioration due to perturbations, sufficient robustness is desired for closed-loop controllers designed based on Equation (12). In other words, robust control methods (e.g., the LPV control method discussed in this work) are expected to be used to conduct control design for the 2-3(F) system.…”
Section: Tensegrity Configurationmentioning
confidence: 99%
“…10 Experiments were conducted to demonstrate the feasibility of stowing thin membranes using the spiral folding technique. 11,12 Tensegrity-membrane systems proposed in the work of Yang and Sultan 13 were designed as candidates for deployable structures in space and civil applications. It was shown that linear/nonlinear feedback controllers could be designed to deploy tensegrity-membrane systems from compact folded shapes based on the tendon control technique, 14,15 while the attached membranes were controlled to be tensioned during system deployment.…”
mentioning
confidence: 99%
“…12 Instead of removing material, it has been proposed to widen and reduce the thickness of the crease regions. 12,13 However, this results in the presence of large voids in the packaged membrane. Crease widths of 10 to 14 times the panel thickness were required in previous studies to enable packaging.…”
Section: Iib 2d Compactionmentioning
confidence: 99%